ANALISIS PENGARUH KEPUASAN PELANGGAN TERHADAP BRAND RELATIONSHIP J.CO DONUTS & COFFEE DI MALL KELAPA GADING JAKARTA UTARA - Lily Harjati (Jurnal Manajemen, 2016)
The growth of competition in Food & Beverage business became rapid, especially in Indonesia dengan with the presence of various Food & Beverage business. One of the company that engaged in Food & Beverage business in Indonesia is J.CO Donuts & Coffee, that is owned by Jhonny Andrean. The first J.CO Donuts & Coffee’s goods opened on 26 June 2005 located at Lippo Karawaci, Indonesia. That’s why, researcher interested to do a research with title The Influence of Consumer Satisfaction To Brand  Relationship at J.CO Donuts & Coffee in Kelapa Gading mall. The theories used to support this research were the definition along with the indiators from Consumer Satisfaction, and Brand Relationship. The object this research was J.CO Donuts & Coffee at Kelapa Gading mall. This research used a questionnaire for data collection and non probability sampling with Judgement Sampling technique. The procedure used to test the model and data processing was Structural Equation Modelling using SPSS Statistic 20. Output generated by SPSS statistic 20 showed that Consumer Satisfaction had positive and significant influence on Brand Relationship. The conclusion of this research is all the hypotheses have proven to have positive and significant influence. Keywords: Customer Satisfaction, Brand Relationship